Dance in times of Pandemics: Questions and Motivations of Moving Bodies - Delgado-Esquivel, Alexandra (2021)
This essay offers a reflection on dance and the way in which physi- cal distancing and adaptation to virtual modalities crosses the artistic work starting from an unexpected context, the search for new scenarios, the problematiza- tion of the teaching/learning processes and the reflections in resistance mode and new cons- tructions of the bodies in movement, their environments and diverse realities